ANALISIS STABILITAS ATMOSFER PADA LAPISAN TROPOSFER ATAS DAN STRATOSFER BAWAH DI ATAS KOTOTABANG MENGGUNAKAN DATA EQUATORIAL ATMOSPHERE RADAR (EAR), BOUNDARY LAYER RADAR (BLR) DAN RADIOSONDE - Eddy Hermawan; Sri Hartati Soeparno; Filla Aulifin Kemirah (Lembaga Penerbangan dan Antariksa Nasional, 2006)
This paper is mainly concerned to the analysis of atmospheric stability especialy near the tropopause layer as well as the variation on wet and dry seasons over Kototabang area, West Sumatera (0.2˚S;100.32˚E) using Equatorial Atmosphere Radar (EAR), Boundary Layer Radar (BLR) and radiosonde data. The Observation of atmosphere stability nearby the tropopauselayer is very important, condering its function as a buffer of an air masses exchanges from troposphere to stratosphere layer and so the contrary, which is usually called as Statosphere - Troposphere Exchange (STE). Data analysis divide in two stages, firstly is the short periode data analysis from Aptil, 10th until May, 9th of 2004 with the main pupose of validation between vertical echo power (VEP) from EAR and Brunt-Vailsala Frequency Squared (N2) from radiosondes. The result shows that the average of correlation coeffisient from 9 observations is 0.81. This point shows that EAR's ability to replace radiosondes data to inform atmosphere stability. The second stage, contain the long periode data analysis from June and November in the years of 2001 until 2004. Both month representing dry and wet seasons based on monthly Global Precipitation Climatology Project (GPCP) data over 25 years (1979-2004) observations in Sumatera Inland area, specifically for Kototabang. Final result shows that the tropopause height variation in dry season (November) is easier to identify. In the other side, zonal wind dominant in November compare to vertical wind on July. This situation probably because the strong monsual affect in wet seasons. The tropopause height is also estimate have no significant effevt to rain intensity.